Desain Feed Instagram Sahwa Pure Water Dengan Pendekatan Komunikasi Persuasif Untuk Menarik Minat Bersedekah - Shabina, Sharah; Aji, Restu Ismoyo (Pusat Riset dan Inovasi Nasional, 2023)
One of the teachings in religion, especially Islam, encourages its followers to give charity to others. Charity is considered an effort to eradicate poverty and provide assistance to fellow human beings. However, in reality, it is often found that some people are reluctant to give charity due to various factors. This includes the belief that charity may diminish their wealth, as well as doubts about giving charity due to concerns about the misuse of funds and whether they will reach the right recipients. Recognizing this, there is a need for a medium that can build awareness of the importance of giving charity. One effective approach is to use social media, such as Instagram, to engage the public and encourage them to contribute. In this context, Sahwa Pure Water utilizes Instagram to invite the target audience to donate. The collected funds will be directed to the visually impaired, the underprivileged, and mosques along travel routes around Surabaya in the form of Sahwa drinking water products. The Instagram feed design of Sahwa Pure Water adopts the concept of persuasive communication theory, consisting of Attention, Interest, Desire, Decision, and Action. This is implemented through the use of techniques such as arrangement, reward, and fear arousing. The campaign can be found on their Instagram account @baikitusahwa.